Kinetics Study on Thermal Degradation of Polystyrene and Sulfonated Polystyrene from Styrofoam Waste - Pramono, Edi; Dewi, Chintya; Rahmawati, Fitria (Molekul, 2023)
This research studied kinetics of thermal degradation of polystyrene (PS), and sulfonated polustyrene (sPS) which were synthesized from styrofoam waste. The thermal study was conducted by thermogravimetric analysis (TGA) at various heating rate of 10, 15, 20 and 25 dpm. The kinetics parameters were determined by Coats Redfern (CR), Friedman (FM), Kissinger-Akahira-Sunose (KAS) and Ozawa-Flynn-Wall (OFW) models. TGA result found that PS has range thermal stability of 274 – 415 oC, but sPS has range thermal stability of 175 – 582 oC. Kinetic study to PS shows that the activation energy increases by the increasing of fraction conversion for all kinetics parameters with a regression value close to 1. While in sPS, the CR method shows an increase in activation energy value with an increasing fraction convertion. On the other hand, CR-FM-KAS and OFM methods obtained an increase in activation energy, then decreased at the fraction convertion above 0.6, and received negative activation energy. The kinetics model successfully explains the degradation of PS and sPS. In addition, the high thermal stability of sPS from styrofoam waste shows that this material has good potential as polymer electrolyte materials.